Multicenter, Randomized Split-Face Trial of a Crosslinked Hyaluronic Acid Filler With Lidocaine for Nasolabial Fold Correction - Frank, Konstantin; Downie, Jeanine; Gold, Michael; Joseph, John; Green, Jeremy; Fabi, Sabrina; Bank, David; Cohen, Joel L; Shamban, Ava; Weiss, Robert; Krames-Juerss, Alice; Monheit, Gary (Aesthetic surgery journal, 2025)
Nasolabial folds (NLFs) are common age-related facial lines, often treated with dermal fillers. Princess® FILLER Lidocaine (PFL; now saypha® filler Lidocaine) and Juvéderm® Ultra XC (JUXC) are both hyaluronic acid-based fillers used for this purpose. To evaluate the effectiveness and safety of PFL in reducing NLF severity compared to JUXC using a split-face study design. In this randomized, subject- and investigator-blinded multicenter study, subjects with moderate to severe NLFs received PFL on one side of the face and JUXC on the other. Baseline NLF severity was assessed using the 5-point Nasolabial Fold Severity Rating Scale (NLF-SRS). Follow-up assessments occurred at weeks 12, 24, 36, and/or 48. The primary endpoint was the proportion of NLF-SRS responders at week 24. Secondary endpoints included assessments by photographic reviewers and treating investigators, along with Global Aesthetic Improvement Scale (GAIS) ratings. Safety was monitored via adverse event reporting and subject diaries. FACE-Q questionnaires evaluated subject satisfaction. Repeat treatment was permitted at week 36 or 48 if needed. At week 24, PFL demonstrated non-inferiority to JUXC (82.2% vs. 81.9% responders; difference 0.37%, p < 0.0001). Secondary assessments confirmed this finding. Adverse events occurred in 24.4% of subjects post-PFL, with most being mild to moderate. Serious TEAEs were rare (1.1%). PFL is a non-inferior alternative to JUXC for treating moderate to severe NLFs, with comparable efficacy, safety, and patient satisfaction.